The Effect of Nutrition Counseling on Increasing Nutritional Literature in Pregnant Women - Herlitawati, Herlitawati (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2022)
Increased nutritional literacy in the form of knowledge and practice of nutrition can stimulate action to meet the nutritional needs of pregnant women. Nutrition counseling is the right strategy for increasing the nutritional literacy of pregnant women. This study aims to analyze the effect of nutritional counseling on increasing nutritional literacy in pregnant women. This type of research is quantitative research using a quasi-experimental method. The design of this research is pre and post-test without control. The research population was all pregnant women in Buah Pala Village, Lawe Sumur District, Southeast Aceh Regency with a total sampling technique of 45 pregnant women. Data were analyzed bivariate using the Wilcoxon test. The results showed that there was an effect of counseling on nutrition on nutritional literacy in pregnant women with Asymp. Sig. (2-tailed) is worth 0.001. The conclusion is that maternal nutritional literacy increased after the provision of nutritional counseling. Therefore, it is expected that health workers will support pregnant women to consume a healthy diet during pregnancy, especially those with low economic status.